2007
DOI: 10.1590/s1516-31802007000400009
|View full text |Cite
|
Sign up to set email alerts
|

Early dexamethasone treatment for septic shock patients: a prospective randomized clinical trial

Abstract: CONTEXT AND OBJECTIVE: Sepsis and septic shock are very common conditions among critically ill patients that lead to multiple organ dysfunction syndrome (MODS) and death. Our purpose was to investigate the effi cacy of early administration of dexamethasone for patients with septic shock, with the aim of halting the progression towards MODS and death. DESIGN AND SETTING:Prospective, randomized, double-blind, single-center study, developed in a surgical intensive care unit at Hospital das Clíni-cas, Faculdade de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 24 publications
4
65
0
1
Order By: Relevance
“…Five randomized clinical trials investigated the effects of prolonged treatment with corticosteroid at moderate doses when initiated within 24 hours of onset of severe sepsis [2,[19][20][21][22][23]. In these trials, 118 deaths occurred among the 222 corticosteroid-treated patients and 139 deaths among the 223 controls (RR=0.85; 95% CI, 0.73-0.99; P=0.03).…”
Section: Clinical Evidence For Use Of Corticosteroids In Sepsismentioning
confidence: 99%
“…Five randomized clinical trials investigated the effects of prolonged treatment with corticosteroid at moderate doses when initiated within 24 hours of onset of severe sepsis [2,[19][20][21][22][23]. In these trials, 118 deaths occurred among the 222 corticosteroid-treated patients and 139 deaths among the 223 controls (RR=0.85; 95% CI, 0.73-0.99; P=0.03).…”
Section: Clinical Evidence For Use Of Corticosteroids In Sepsismentioning
confidence: 99%
“…A randomized study enrolled 29 patients with septic shock who received 0.2 mg/kg dexamethasone or placebo (3 times every 36 h) and reported signifi cantly faster shock reversal, reduced 7-day mortality (67% vs 21%), and a trend toward reduction in 28-day mortality [ 16 ]. An open-label, randomized study investigated a 3-day therapy with methylprednisolone, 40 mg, in 31 patients with community-acquired pneumonia and reported shorter requirement for antibiotic use and faster resolution of clinical symptoms [ 17 ].…”
Section: Other Recent Trialsmentioning
confidence: 99%
“…4 concluded that early treatment with dexamethasone reduced the seven-day mortality among septic shock patients and showed a trend towards reduction of 28-day mortality. Ribeiro et al 5 hope to suggest methodologies that will enable physicians to promote regular physical activity at appropriate levels, ensuring various benefits for the individual over the short, medium and long terms, which determines their importance in the promotion of health.…”
Section: Discussionmentioning
confidence: 99%